Tapering body stiffness shortens upper gastrointestinal examination via transoral insertion with ultrathin endoscope - Ono, Satoshi; Ito, Shun; Maejima, Kyohei; Hosaka, Shosuke; Umeki, Kiyotaka; Sato, Shin-ichiro (Endoscopy International Open, 2020)
Background and study aims Ultrathin endoscopes are commonly used for surveillance esophagogastroduodenoscopy (EGD) to reduce discomfort associated with scope insertion. However, the flexibility of an ultrathin endoscope is a trade-off between reducing discomfort and lengthening examination time.Patients and methods The EG17-J10 (EG17) is a novel ultrathin endoscope characterized by its tapering body stiffness; however, the flexibility of its tip is comparable to that of the traditional ultrathin endoscope EG16-K10 (EG16). We compared EGD examination time between EG17 and EG16. A total of 319 examinees who underwent EGD from November 2019 to January 2020 at the Chiba-Nishi General Hospital were enrolled. Six examinees were excluded due to past history of surgical resection of the upper gastrointestinal tract or too much food residues; 313 examinees (EG17, 209; EG16,104) were retrospectively analyzed. The examination time was divided into three periods: esophageal insertion time (ET), gastroduodenal insertion time (GDT), and surveillance time of the stomach (ST). The total amount of ET, GDT, and ST was defined as total examination time (TT).Results TT of EGD using EG17 was significantly shorter compared to EGD using EG16 (222.7 ± 68.9 vs. 245.7 ± 78.5 seconds) (P = 0.004). Among the three periods of examination time, ET (66.7 ± 24.1 vs. 76.0 ± 24.1 seconds) (P = 0.001) and GDT (47.9 ± 17.4 vs. 55.2 ± 35.2 seconds) (P = 0.007) of EGD using EG17 were significantly shorter compared to EGD using EG16, except for ST (108.1 ± 51.5.1 vs. 114.5 ± 50.1 seconds) (P = 0.148).Conclusion An ultrathin endoscope with tapering body stiffness can shorten EGD examination time, mainly due to the shortening of insertion time.